The eﬀect of Wii Fit exergames on balance in the elderly: a scoping review - Fadila, Dhira Rahma; Rahman, Farid (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. The elderly are increasingly embracing exercise through video or virtual reality games, such as sports games on platforms like Wii Fit. Additional proof about the speciﬁc dosage and types of Wii Fit games that might eﬀectively enhance balance in older individuals is required. This scoping study investigated the eﬃcacy of Wii Fit in improving body balance in older adults, including static and dynamic balance.Methods. The study used PRISMA Extension for Scoping Review guidelines, conducting systematic searches across Scien-ceDirect, PubMed, and Google Scholar from January 2011 to August 2023. The quality assessment employed various tools tailored to study types, including the Joanna Briggs Institute, Case Report Guidelines, and Physiotherapy Evidence Database. Data synthesis was facilitated by the TIDIer checklist, encompassing extraction of population, intervention, and outcome meas-ures from 21 articles.Results. Of the 1,170,131 studies found in the databases, 258 were selected after reviewing the titles and abstracts, and 21 articles were included in the study after examining the full text. The reviewed articles showed that, although there were varia-tions in the Wii Fit balance exercise programme, regular and structured administration of Wii Fit signiﬁcantly aﬀected balance.Conclusions. The study suggests that incorporating Wii Fit into elderly ﬁtness routines can notably enhance balance and po-tentially lower fall risk.
Keywords: elderly; balance; fall risk; virtual reality; Nintendo Wii Fit